2019
DOI: 10.1016/j.cell.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation Blocks cGAS Activity and Inhibits Self-DNA-Induced Autoimmunity

Abstract: Highlights d Acetylation suppresses cGAS activity d Aspirin directly acetylates cGAS d Aspirin inhibits cGAS-mediated interferon production d Aspirin alleviates DNA-induced autoimmunity in AGS mouse models and patient cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
268
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(288 citation statements)
references
References 63 publications
7
268
0
2
Order By: Relevance
“…In addition, novel small molecules such as RU320521 or G150 can occupy the enzymatic pocket of species-specific cGAS to abrogate cGAMP synthesis (272,273). Recently, a study found that aspirin can acetylate cGAS at three lysine residues and block cGAS activity (274). With regard to STING, the cyclopeptide Astin C can block IRF3 recruitment onto the STING signalosome (275).…”
Section: Targeting the Cgas-sting Pathway For Treatmentmentioning
confidence: 99%
“…In addition, novel small molecules such as RU320521 or G150 can occupy the enzymatic pocket of species-specific cGAS to abrogate cGAMP synthesis (272,273). Recently, a study found that aspirin can acetylate cGAS at three lysine residues and block cGAS activity (274). With regard to STING, the cyclopeptide Astin C can block IRF3 recruitment onto the STING signalosome (275).…”
Section: Targeting the Cgas-sting Pathway For Treatmentmentioning
confidence: 99%
“…The cGAS N-terminal tail has been implicated in DNA interactions, protein stability, localization, and higher-order complex formation, suggesting that these extensions are important to regulate enzyme activation [10,39 ,41-43]. In addition to oligomerization, CD-NTase function is further regulated by intrinsic species-specific substitutions that fine-tune enzyme activation [29 ,44], additional domains like tandem arrays of the CD-NTase module or fusion to ubiquitin-like proteins in some OAS homologs [45], and post-translational modifications [46][47][48].…”
Section: Structural Anatomy Of Cd-ntase Enzymesmentioning
confidence: 99%
“…Knockout studies have shown that Trex1 null mice, which have elevated interferon levels, return to WT levels of interferon upon knockout of cGAS 38,39 , STING 40,41 , or IRF3 40 . These studies further validate the importance of cGAS and its role in regulating immunity, and it has become a prime candidate for the development of small molecules that activate or inhibit its immunopotent activity 42,43,44,45 . Identifying an effective cGAS inhibitor could serve as a tool to help assess the contribution of the cGAS-STING signaling axis in various immune responses, and could ultimately serve as a chemical scaffold towards the development of clinical compounds for the treatment of associated autoimmune diseases.…”
Section: Introductionmentioning
confidence: 65%
“…Given the importance of the cGAS pathway to stimulating the innate immune system, a number of agonists and antagonists have been generated in attempts to probe the molecular underpinnings and to manipulate activity for therapeutic intervention 53,43,54,45,44 . While in vitro studies have difficulties in showing that RU.521 can inhibit recombinant human cGAS 47,44 , our data here indicate that RU.521 does inhibit human cGAS activity in cells.…”
Section: Discussionmentioning
confidence: 99%